Conductive agent for electrodes, composition for electrodes, and electrodes for lithium ion batteries
By using flake graphite with specific characteristics in lithium-ion battery electrodes, the challenges of potential drops and corrosion are addressed, resulting in improved battery capacity, charging time, and lifespan.
Patent Information
- Application Number
- JP2021561542
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-29
- Filing Date
- 2020-11-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2040-11-27
AI Technical Summary
Existing lithium-ion battery electrodes face challenges in suppressing potential drops and corrosion of the current collector, especially when increasing the nickel content in the active material to enhance battery capacity and reduce charging time.
Incorporating flake graphite with specific characteristics, such as a band intensity ratio of Raman spectra ≥8, a G-band half-maximum width of 15-22 cm^-1, and a basal surface thickness of 5-40 nm, into the electrode composition without special surface treatment, significantly improves conductivity and reduces interface resistance.
This approach results in a lithium-ion battery with reduced volume resistivity, enhanced discharge capacity, suppressed potential drops, and minimized corrosion of the current collector, leading to improved battery capacity, shorter charging times, and extended battery life.
Smart Images

Figure 0007650458000005 
Figure 0007650458000006 
Figure 0007650458000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive agent for an electrode, a composition for an electrode, and an electrode for a lithium ion battery. [Background technology]
[0002] In recent years, small, lightweight, and large-capacity lithium-ion batteries have been used in mobile phones, digital cameras, etc. Lithium-ion batteries are also being developed as large secondary batteries for use in electric vehicles, but there is a demand for higher battery capacity, shorter charging times, and improved battery life in order to extend the driving range while maintaining safety and reliability.
[0003] The electrodes of lithium-ion batteries are positive or negative electrodes in which a mixture containing an electrode active material, a conductive agent, and a binder is applied to the surface of a metal foil current collector. In the positive electrode, a lithium-containing metal composite oxide or the like is used as the active material, and in order to improve the effective capacity of the battery, active materials with a higher nickel content in the metal composite oxide are being investigated.
[0004] However, increasing the nickel content in the metal composite oxide increases the effective capacity of the battery, but increases the interfacial resistance between the current collector and the active material, and the volume resistance between the active materials, causing a potential drop. Furthermore, if charging is continued in a state where a potential drop has occurred, active oxygen is generated due to a reaction between oxygen derived from the active material and alkaline components. As a result, there is a problem that the current collector foil corrodes and the battery life is shortened.
[0005] In order to improve the conductivity of lithium-ion batteries, electrodes made of graphene or exfoliated graphite have also been proposed (Patent Documents 1 and 2). For example, Patent Document 1 describes the I measured by Raman spectroscopy. D Peak / I GA lithium ion secondary battery element is disclosed that uses laminated graphene powder having a peak intensity ratio of 0.3 to 2.8 as a conductive agent. In this Patent Document 1, the laminated graphene powder is produced by subjecting graphite to a special surface treatment such as oxidation and reduction in order to enhance the dispersibility of the laminated graphene powder in an organic solvent. In addition, Patent Document 2 discloses a secondary battery electrode forming material that uses flake graphite as a conductive agent.
[0006] However, even with these conventional methods, it is necessary to simultaneously increase the nickel content in the active material to improve the battery capacity, while suppressing the potential drop and suppressing corrosion of the current collector due to the generation of active oxygen. It has been desired to further shorten the charging time and further improve the battery life.
[0007] [Patent Document 1] Special Publication No. 2014-505002 [Patent Document 2] JP 2014-182873 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a conductive agent for electrodes of lithium ion batteries, a composition for electrodes, and an electrode that can suppress potential drop and corrosion of current collecting foils even when the content ratio of nickel in the active material is increased, and as a result, can achieve high battery capacity, shortened charging time, and improved battery life. [Means for solving the problem]
[0009] As a result of intensive research to solve the above problems, the inventors discovered that by incorporating exfoliated graphite having specific characteristics into a composition for electrodes of lithium ion batteries, the above object of the present invention can be achieved without subjecting the graphite to a special surface treatment, and thus completed the present invention.
[0010] That is, the present invention is a conductive agent for an electrode of a lithium ion battery, comprising: ~(3) Exfoliated graphite having the following characteristics: (However, active materials are excluded.) The present invention provides a conductive agent comprising: (1) The band intensity ratio of the Raman spectrum measured by Raman spectroscopy using an argon laser satisfies the following relationship: [G band (1580cm -1 ) Intensity / D band (1360cm -1 ) Intensity ≧8 (2) Raman spectrum G band (1580 cm) measured by Raman spectroscopy using an argon laser -1 ) half width (G-FWHM) is 15-22cm -1 is (3) The thickness of the basal surface of the exfoliated graphite particles is 5 to 40 nm, as measured by a field emission scanning electron microscope (FE-SEM).
[0011] The present invention also relates to the above (1) ~(3) Exfoliated graphite having the following characteristics: (However, active materials are excluded.) and a binder. The present invention also provides an electrode for a lithium ion battery, comprising a current collector coated with the electrode composition of the present invention. The present invention also provides a method for producing an electrode for a lithium ion battery, which comprises applying the electrode composition of the present invention onto a current collector. Furthermore, the present invention provides a lithium ion battery comprising the electrode of the present invention. Effect of the Invention
[0012] By using the specific ultra-thin graphite of the present invention as a conductive agent, it is possible to significantly reduce the volume resistivity and produce an electrode composition with a significantly improved discharge capacity without the need for a special surface treatment of the graphite as in the conventional method. Therefore, even if the content ratio of nickel in the active material is increased, the potential drop can be suppressed, and as a result, the corrosion of the current collector foil can be suppressed. Therefore, it is possible to provide a conductive agent for electrodes, an electrode composition, and an electrode for lithium ion batteries that can achieve high battery capacity, short charging time, and improved battery life. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a graph showing the results of measuring the initial discharge capacity of coin cells produced using electrode compositions 1 and 3 produced in Example 1 and Comparative Example 2. [Diagram 2] FIG. 2 is a graph showing the results of measuring the discharge capacity after 80 cycles when coin cells were produced using electrode compositions 1 and 3 produced in Example 1 and Comparative Example 2. [Diagram 3] FIG. 13 is a graph showing the results of measuring the initial discharge capacity of coin cells produced using electrode compositions 4 and 5 produced in Example 2 and Comparative Example 3. [Figure 4] FIG. 13 is a graph showing the results of measuring the discharge capacity after 80 cycles when coin cells were produced using electrode compositions 4 and 5 produced in Example 2 and Comparative Example 3. [Diagram 5] FIG. 13 is a graph showing the results of measuring the initial discharge capacity of coin cells produced using electrode compositions 6 and 7 produced in Example 3 and Comparative Example 4. [Figure 6] FIG. 13 is a graph showing the results of measuring the discharge capacity after 80 cycles when coin cells were produced using electrode compositions 6 and 7 produced in Example 3 and Comparative Example 4. [Figure 7] FIG. 1 is a cross-sectional view that illustrates a lithium-ion battery produced using an electrode composition 1 (Example 1) of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Representative embodiments for carrying out the present invention will be described in detail below, but the present invention is not limited to the following embodiments.
[0015] (exfoliated graphite) The present invention is characterized by using exfoliated graphite having the following characteristics (1) and (2) as an electrode conductive agent for a lithium secondary battery. (1) The band intensity ratio of the Raman spectrum measured by Raman spectroscopy using an argon laser satisfies the following relationship: [G band (1580cm -1 ) Intensity / D band (1360cm -1 ) Intensity ≧8 (2) Raman spectrum G band (1580 cm) measured by Raman spectroscopy using an argon laser -1 ) half width (G-FWHM) is 15-22cm -1 It is. In the present invention, the conductive agent means a material that contributes to the conductivity of an electrode, and the exfoliated graphite of the present invention has the function of further reducing the resistance of the electrode and further improving the conductivity.
[0016] (Feature (1): Band intensity ratio of Raman spectrum) When the exfoliated graphite of the present invention is measured by Raman spectroscopy using an argon ion laser (excitation wavelength 532 nm), it has a G band in the Raman spectrum (1580 cm -1 ) and D band (1360cm -1 ) The intensity ratio satisfies the following relationship: [G band (1580cm -1 ) Intensity / D band (1360cm -1 ) Intensity ≧8
[0017] Here, the G band of the Raman spectrum (1580 cm -1 ) and D band (1360cm -1 ) indicates the crystallinity of graphite (basal surface). In the present invention, the band intensity ratio (G band / D band) is the baseline (1500-1650 cm ) of the G band in a Raman spectrum measured under the conditions of an output of 0.5 mW, an exposure time of 5 Hz (0.2 s), and 1000 scans (accumulation). -1 ) and the baseline of the D band (1300-1400 cm -1 ) are plotted as straight lines, and the peak heights of the G band and D band from the baseline are then determined and applied to the following formula to calculate the ΔG. Band intensity ratio = G band peak height / D band peak height
[0018] The band intensity ratio (G band / D band) of the exfoliated graphite of the present invention is measured in accordance with Japanese Industrial Standard JIS K 0137-2010, and specifically, from the viewpoint of maintaining the crystallinity of the exfoliated graphite, the lower limit is preferably 8.2 or more, 8.4 or more, 8.6 or more, more preferably 8.8 or more, and particularly preferably 9.0 or more, and the upper limit is preferably 25 or less, 23 or less, 20 or less, more preferably 15 or less, and particularly preferably 13 or less. The upper and lower limits of the band intensity ratio can be arbitrarily combined.
[0019] (Feature (2): Raman spectrum G band half-width (G-FWHM)) When the exfoliated graphite of the present invention is measured by Raman spectroscopy using an argon ion laser (excitation wavelength 532 nm), it has a G band in the Raman spectrum (1580 cm -1 ) half width (G-FWHM) is 15-22cm -1 Here, G band (1580 cm -1 ) indicates the crystallinity of graphite.
[0020] In the present invention, the half-width of the G band (G-FWHM) is measured in accordance with the Japanese Industrial Standard JIS K 0137-2010 "General Rules for Raman Spectroscopic Analysis". Specifically, in a Raman spectrum measured under conditions of an output of 0.5 mW, an exposure time of 5 Hz (0.2 s), and 1000 scans (accumulation), the baseline of the G band (1500-1650 cm -1 ) is drawn as a straight line, the peak height of the G band from the baseline is then determined, and the band width at 50% of the determined peak height can be calculated as the half-width.
[0021] The lower limit of the half width at half maximum (G-FWHM) of the G band of the exfoliated graphite of the present invention is preferably 15.0 or more, 15.5 or more, 16.0 or more, more preferably 16.5 or more, and particularly preferably 17.0 or more, and the upper limit is 21.5 cm -1 Below, 21.0cm -1 Less than 20.5cm, more preferably -1 Less than 20.0 cm is particularly preferable. -1 The upper and lower limits of the G-band full width at half maximum (G-FWHM) can be combined arbitrarily.
[0022] (Average particle size of exfoliated graphite) The exfoliated graphite of the present invention usually has an average particle size in the range of 0.5 to 20 μm when measured by a laser diffraction / scattering method. Here, the average particle size refers to the average value of the longest diameter of the laminated graphene sheet plane in the primary particles. The average particle size can be measured using, for example, Microtrac MT3000II series (manufactured by Microtrac Bell Co., Ltd.) after the exfoliated graphite is sufficiently dispersed.
[0023] In the present invention, the average particle size of the exfoliated graphite measured as described above is preferably 0.8 to 15 μm, more preferably 1.0 to 10 μm, and even more preferably 1.5 to 5 μm, from the viewpoint that the particles as the conductive agent are arranged randomly rather than in a single line, thereby reducing both the plane resistance and the penetration resistance.
[0024] (Thickness of exfoliated graphite particles) The exfoliated graphite of the present invention preferably has a basal plane of the particle having a thickness in the range of 5 to 50 nm as measured by a field emission scanning electron microscope (FE-SEM). In the present invention, the basal plane refers to a layering plane when graphene is layered to form graphite. The thickness of the basal plane of the exfoliated graphite particles of the present invention can be determined by measuring an image of the exfoliated graphite with FE-SEM and measuring the thickness of 10 arbitrarily selected particles with a scale, and averaging the measured values.
[0025] The thickness of the exfoliated graphite particles of the present invention measured in this manner is preferably 5 to 40 nm, more preferably 5 to 30 nm, and particularly preferably 10 to 15 nm, from the viewpoint that even if the flake graphite is physically thinned to the limit by cleavage and crushing, the particles do not retain the properties of single-layer graphene. Ordinary graphite has a structure in which many graphenes (0.335 nm thick) are laminated, and the thickness is usually 500 to 2000 nm. The exfoliated graphite of the present invention is graphite obtained by exfoliating ordinary graphite, and usually has a structure in which 10 to 100 layers of graphene are laminated.
[0026] Moreover, the exfoliated graphite of the present invention preferably has a full width at half maximum (FWHM) measured by a field emission scanning electron microscope (FE-SEM) in the range of 5 to 25 nm. Here, the full width at half maximum (FWHM) refers to the number of points x where g(x) is half the value of the extreme value h when a local response curve g(x)=f(x)-b(x) in the vicinity of a point where f(x) is at an extreme value is considered, in a response curve y=f(x) of y representing the particle size distribution to x. b and x a This refers to the difference between The full width at half maximum (FWHM) of the exfoliated graphite of the present invention is preferably 8 to 22 cm from the viewpoint that the basal plane is not damaged. -1 and particularly preferably 10 to 20 cm -1 It is.
[0027] The exfoliated graphite of the present invention is preferably one that does not have a reactive functional group selected from the group consisting of a hydroxyl group, a carbonyl group, and a methine group on its surface. Conventional laminated graphene powders produced by subjecting graphite to special surface treatments such as oxidation and reduction have reactive functional groups on their surfaces, but the exfoliated graphite of the present invention has good dispersibility in organic solvents even without such reactive functional groups, and can significantly reduce the volume resistivity and significantly improve the discharge capacity.
[0028] The exfoliated graphite of the present invention can be produced by shear-pulverizing and delaminating ordinary graphite using a pulverizer by a wet bead mill method. Zirconia, alumina balls, etc. can be used as beads in the pulverizer, and the diameter of the beads is usually 0.05 to 10 mm, preferably 0.1 to 5 mm, and more preferably 0.3 to 5 mm. The pulverization time is usually 10 minutes to 10 hours, preferably 20 minutes to 7 hours, and more preferably 30 minutes to 5 hours for a volume of 30 to 100 liters.
[0029] In addition, when performing the pulverization treatment by the wet bead mill method, it is preferable to have a suitable dispersant present in order to sufficiently increase dispersibility. As the dispersant, it is preferable to use polyvinyl butyral (PVB), polyvinylpyrrolidone (PVP), carboxymethyl cellulose (CMC), etc. When carboxymethyl cellulose (CMC) is present as a dispersant in the pulverization treatment, the amount of carboxymethyl cellulose (CMC) used is preferably 0.2 to 15.0 parts by weight per 100 parts by weight of graphite to be pulverized.
[0030] The exfoliated graphite produced by such a pulverization method has a very low volume resistivity of 15.0 Ω·cm or less, preferably 10.0 Ω·cm or less, more preferably 8.0 Ω·cm or less, and even more preferably 7.0 Ω·cm or less, when the volume resistivity is measured using a commercially available volume resistivity measuring device in accordance with Japanese Industrial Standard JIS K 7194.
[0031] When ultra-thin exfoliated graphite having the above characteristics (1) and (2) is added to an electrode composition, a physical conductive path is easily formed between the current collector and the active material, reducing the interface resistance, improving the current flow between the active materials, reducing the volume resistance, and suppressing the potential drop, compared to when a conventional conductive agent such as graphene or graphite is added. As a result, the generation of active oxygen can be suppressed, and the corrosion of the current collector foil can be suppressed.
[0032] (Composition for electrode) A composition (conductive paste) containing the exfoliated graphite of the present invention, a binder, and, if necessary, a conductive agent other than the exfoliated graphite of the present invention and a solvent can be used as an electrode composition for lithium ion batteries. As the binder, a binder that has been conventionally used in the manufacture of electrodes, such as polyvinylidene fluoride (PVDF), polyimide (PI), acrylic emulsion, and styrene-butadiene rubber (SBR), can be used. As the conductive agent other than the exfoliated graphite of the present invention, carbon black and carbon nanotubes (CNT) can be mentioned, and among them, carbon black is preferable from the viewpoint of purity and conductivity. As the solvent, an organic solvent such as N-methylpyrrolidone (NMP) or an aqueous solvent containing water can be used. Such a conductive paste not containing an active material can be used as an electrode composition to be mixed with an active material when producing an electrode for a lithium ion battery.
[0033] When used as a conductive paste, the concentration of exfoliated graphite in the electrode composition is usually 1 to 30% by weight, preferably 2 to 20% by weight, and more preferably 2 to 15% by weight. The weight ratio of the conductive agent other than exfoliated graphite to the exfoliated graphite is usually 5:95 to 50:50, preferably 10:90 to 45:55, and more preferably 10:90 to 30:70. The concentration of the binder in the electrode composition is usually 1 to 20% by weight, preferably 2 to 10% by weight, and more preferably 2 to 9% by weight.
[0034] The electrode paste obtained by incorporating the positive or negative electrode active material into the above conductive paste can be used as a composition (mixture) for an electrode to be applied onto a current collector, dried, and adhered when manufacturing the electrode of a lithium-ion battery.
[0035] In the present invention, as the positive electrode active material, a Li-containing composite oxide represented by the composition formula LixMO2 or LiyM2O4 (M is a transition element; 0 < x ≤ 1, 0 < y ≤ 2) can be used. Specific examples of the Li-containing composite oxide include LiCoO2, LiMnO2, LiNiO2, LiCrO2, and LiMn2O4. Since the present invention can suppress the potential drop even when increasing the nickel content ratio in the active material, as the positive electrode active material, a lithium-containing metal composite oxide containing nickel and represented by the composition formula LiNi x Co y Mn z O2 (wherein x, y, and z are the molar ratios of Ni, Co, and Mn, respectively, x + y + z = 1, and 0.5 ≤ x ≤ 0.9) is preferably used. Among them, according to the present invention, a lithium-containing metal composite oxide in which the molar ratio x of Ni in the above composition formula is in the range of 0.5 to 0.9, preferably 0.6 to 0.8, can be used.
[0036] In the present invention, as the negative electrode active material, carbon compounds such as graphite, hard carbon, and coke, silicon, tin-based alloys, lithium titanate (Li4Ti5O 12 ) etc. can be mentioned. Among them, from the viewpoint of safety, graphite or lithium titanate is preferable.
[0037] The composition of the electrode composition when used as an electrode paste is usually 0.2 to 5.5 parts by weight, preferably 0.3 to 5.0 parts by weight, more preferably 0.4 to 4.0 parts by weight, exfoliated graphite is usually 0.2 to 5.5 parts by weight, preferably 0.3 to 3.5 parts by weight, more preferably 0.5 to 3.0 parts by weight, and binder is usually 1.0 to 9.5 parts by weight, more preferably 1.5 to 7.8 parts by weight, per 100 parts by weight of electrode active material. The concentration of exfoliated graphite in the electrode composition is usually 0.2 to 15% by weight, preferably 0.5 to 12% by weight, more preferably 0.7 to 9% by weight, per 100 parts by weight of electrode active material. In the electrode composition, the weight ratio of the conductive agent other than exfoliated graphite to exfoliated graphite is usually 5:95 to 50:50, preferably 10:90 to 45:55, and more preferably 10:90 to 30:70.
[0038] The electrode paste (electrode composition) can be prepared, for example, by mixing a positive or negative electrode active material and the exfoliated graphite of the present invention, and, if necessary, a conductive agent other than the exfoliated graphite of the present invention, with a solution of PVDF dissolved in an organic solvent such as NMP, or a suspension of acrylic emulsion or carboxymethyl cellulose (CMC) dispersed in water.
[0039] (electrode) The electrode for a lithium ion battery of the present invention can be prepared by applying an electrode composition (electrolytic paste) onto a current collector in the same manner as in conventional electrodes, except that the exfoliated graphite of the present invention is used as a conductive agent. For example, a slurry-like electrode composition (electrolytic paste) in which each component is dispersed in an organic solvent such as NMP or an aqueous solvent containing water is applied onto a metal current collector by a doctor blade method, and the solvent is dried to prepare a positive electrode or a negative electrode. As in conventional cases, metals such as aluminum and copper are preferably used as the current collector.
[0040] In the present invention, the interfacial resistance between the current collector and the active material can be further reduced by using a composition containing exfoliated graphite having the above characteristics (1) and (2) as a primer composition for an electrode of a lithium ion battery. In the present invention, the primer or primer layer is an adhesive layer applied between the current collector and the electrode composition layer (electrode mixture layer). Specifically, a primer composition containing another conductive agent such as carbon black and the exfoliated graphite of the present invention is applied to the current collector and dried to form a primer layer on the current collector, and then the electrode composition (electrolytic paste) of the present invention described above is applied to the primer layer, thereby producing an electrode for a lithium ion battery having a lower volume resistivity of the interfacial resistance and high adhesion between the current collector and the electrode mixture layer. In the primer composition of the present invention, the content of exfoliated graphite relative to other conductive agents is usually 10 to 1000 parts by weight, preferably 15 to 750 parts by weight, and more preferably 20 to 600 parts by weight. The thickness of the primer layer is usually 0.5 to 10 μm, and preferably 0.5 to 5.0 μm. When preparing an electrode for a lithium ion battery, if an electrode composition containing the exfoliated graphite of the present invention is used, the primer composition does not need to contain the exfoliated graphite of the present invention, and the primer composition may contain a conductive agent other than the exfoliated graphite of the present invention, such as carbon black, or a known conductive agent.
[0041] A lithium ion secondary battery can be produced by combining the above-mentioned positive electrode and negative electrode with a separator separating the two electrodes, a positive electrode lead, a negative electrode lead, a positive electrode external terminal, and a negative electrode can. As the electrolyte, an electrolytic solution or a solid electrolyte can be used. As the electrolytic solution, an organic electrolyte solution in which LiPF6 is dissolved in a mixed solvent of cyclic carbonate esters such as ethylene carbonate (EC) or propylene carbonate (PC) and chain carbonate esters such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), or diethyl carbonate (DEC) can be used. As the solid electrolyte, an inorganic solid electrolyte such as an oxide or sulfide solid electrolyte, or an organic solid electrolyte such as a polymer solid electrolyte can be used. EXAMPLES
[0042] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples.
[0043] [Production of exfoliated graphite] (Production Examples 1 to 3) High purity graphite (J-SP-α manufactured by Nippon Graphite Industries Co., Ltd., average particle size: 6.1 μm) was pulverized by a wet bead mill method using a pulverizer (NVM-30) manufactured by Imex Corporation under conditions 1 to 3 shown in Table 1 below.
[0044] [Table 1]
[0045] The Raman spectrum band intensity ratio (G band / D band), G band half-width (G-FWHM), average particle size, particle thickness, and volume resistivity of the exfoliated graphite obtained by pulverization processing under conditions 1 to 3 were measured under the conditions below, and the results are shown in Table 2.
[0046] (1) Band intensity ratio (G band / D band) The measurement was performed in accordance with JIS K 0137-2010 "General Rules for Raman Spectroscopic Analysis." That is, in the Raman spectrum measured by Raman spectroscopic analysis using an argon laser under the conditions of output of 0.5 mW, exposure time of 5 Hz (0.2 s), and scan (accumulation) of 1000 times, the baseline of the G band (1500-1650 cm -1 ) and the baseline of the D band (1300-1400 cm -1 ) were plotted as straight lines, and the peak heights of the G band and D band from the baseline were then determined. The band intensity ratio (G band / D band) was calculated by applying the following formula: Band intensity ratio = G band peak height / D band peak height
[0047] (2) G-band full width at half maximum (G-FWHM) The measurements were performed in accordance with JIS K 0137-2010 "General Rules for Raman Spectroscopic Analysis." That is, in the Raman spectrum measured under the conditions of an output of 0.5 mW, an exposure time of 5 Hz (0.2 s), and 1000 scans (accumulation), the baseline of the G band (1500-1650 cm -1 ) was drawn as a straight line, the peak height of the G band from the baseline was then determined, and the band width at 50% of the determined peak height was calculated as the half-width.
[0048] (3) Average particle size (μm) The average longest diameter of the stacked graphene sheet planes in the primary particles was measured by the laser diffraction / scattering method using a Microtrac MT3000II series (Microtrac Bell Corporation).
[0049] (4) Particle thickness (nm) The image of exfoliated graphite was measured using a FE-SEM, and the thickness of 10 arbitrarily selected particles was measured using a scale, and the average value was calculated.
[0050] (5) Volume resistivity (Ω·cm) was measured in accordance with JIS K 7194 using a commercially available volume resistivity measuring device.
[0051] [Table 2]
[0052] [Preparation and evaluation of electrode composition] (Example 1, Comparative Examples 1 and 2) Lithium cobalt manganese composite oxide (LiNi 0.8 Co 0.1 Mn 0.1O2), carbon black as a conductive agent (acetylene black Li250 manufactured by Denka Co., Ltd.), exfoliated graphite manufactured in Manufacturing Example 3 (condition 3), and PVDF#7300 (manufactured by Kureha Co., Ltd.) as a binder were dispersed in an NMP solution so that the solids weight ratio of the active material, carbon black (conductive agent), exfoliated graphite (conductive agent), and binder was 94.4:1.3:2.3:2.0 to form a slurry (solids concentration 65% by weight), and an electrode composition 1 (Example 1) was prepared. The concentration of exfoliated graphite in the electrode composition at this time was 1.5% by weight.
[0053] In addition, electrode composition 2 (Comparative Example 1) was prepared in the same manner as electrode composition 1, except that the exfoliated graphite was changed to ordinary graphite (J-SP-α manufactured by Nippon Graphite Industry Co., Ltd.). Furthermore, electrode composition 3 (Comparative Example 2) was prepared in the same manner as electrode composition 1, except that no exfoliated graphite (conductive agent) was used and the solid weight ratio of the active material, conductive agent, and binder was 93.0:3.5:3.5.
[0054] The electrode compositions 1 to 3 thus prepared were subjected to volume resistivity measurement, and the results are shown in Table 3 below.
[0055] [Table 3]
[0056] From the results in Table 3, it was confirmed that the volume resistivity increases in the case of electrode composition 2 (Comparative Example 1), which uses ordinary graphite and carbon black as the conductive agents, compared to electrode composition 3 (Comparative Example 2), which does not use graphite as the conductive agent, whereas the volume resistivity can be significantly reduced in the case of electrode composition 1 (Example 1), which uses the exfoliated graphite and carbon black of the present invention as the conductive agents.
[0057] Coin cells were prepared using electrode compositions 1 and 3 in accordance with the coin cell CR2032 specified in the Japanese Industrial Standard JIS C 8515. The initial discharge capacity and the discharge capacity after 80 cycles were measured at an upper limit voltage of 4.3 V and a lower limit voltage of 2.7 V. The results are shown in Figures 1 and 2, respectively.
[0058] From the results in FIG. 1, it was confirmed that when electrode composition 3 (Comparative Example 2) was used, the initial discharge capacity was 187 mAh / g, whereas when electrode composition 1 (Example 1) was used, the initial discharge capacity was 195 mAh / g, and that the initial discharge capacity of electrode composition 1 (Example 1) was increased by approximately 4.3% compared to when electrode composition 3 (Comparative Example 2) was used.
[0059] From the results in FIG. 2, it was confirmed that when electrode composition 3 (Comparative Example 2) was used, the discharge capacity after 80 cycles was 155 mAh / g, whereas when electrode composition 1 (Example 1) was used, the discharge capacity was 163 mAh / g. In other words, when electrode composition 1 (Example 1) was used, the discharge capacity after 80 cycles was increased by approximately 5.2% compared to when electrode composition 3 (Comparative Example 2) was used. These results show that the use of an organic solvent-based positive electrode composition containing the exfoliated graphite of the present invention as a conductive agent significantly increases the discharge capacity and improves the cycle characteristics.
[0060] (Example 2 and Comparative Example 3) Lithium iron phosphate (LFP) as a positive electrode active material, carbon black (acetylene black Li250 manufactured by Denka Co., Ltd.) as a conductive agent, exfoliated graphite manufactured in Manufacturing Example 3 (condition 3), and acrylic emulsion and carboxymethyl cellulose (CMC) as a binder were dispersed in ion-exchanged water so that the solid weight ratio of the active material, carbon black (conductive agent), exfoliated graphite (conductive agent), and binder was 94.4:1.3:2.3:2.0 to form a slurry (solid concentration 55% by weight), and an electrode composition 4 (Example 2) was prepared. In addition, an electrode composition 5 (Comparative Example 3) was prepared in the same manner as the electrode composition 4, except that the conductive agent was changed to only carbon black (acetylene black Li250 manufactured by Denka Co., Ltd.).
[0061] In accordance with the coin cell CR2032 specified in the Japanese Industrial Standard JIS C 8515, a primer composition containing exfoliated graphite and carbon black as conductive agents and acrylic resin as adhesive was applied onto a current collector and dried to form a primer layer on the current collector. Next, electrode compositions 4 and 5 were used as the positive electrode compositions to prepare coin cells. The initial discharge capacity and the discharge capacity after 80 cycles were measured at an upper limit voltage of 3.6 V and a lower limit voltage of 2.0 V. The results are shown in Figures 3 and 4, respectively.
[0062] From the results in FIG. 3, it was confirmed that when electrode composition 5 (Comparative Example 3) was used, the initial discharge capacity was 118 mAh / g, whereas when electrode composition 4 (Example 2) was used, the initial discharge capacity was 133 mAh / g, and that the initial discharge capacity of electrode composition 4 (Example 2) was increased by approximately 12.7% compared to when electrode composition 5 (Comparative Example 3) was used.
[0063] From the results in FIG. 4, it was confirmed that when electrode composition 5 (Comparative Example 3) was used, the discharge capacity after 80 cycles was 108 mAh / g, whereas when electrode composition 4 (Example 2) was used, the discharge capacity was 130 mAh / g. In other words, when electrode composition 4 (Example 2) was used, the discharge capacity after 80 cycles was increased by approximately 20.4% compared to when electrode composition 5 (Comparative Example 3) was used. These results show that the use of an aqueous positive electrode composition containing the exfoliated graphite of the present invention as a conductive agent significantly increases the discharge capacity and improves the cycle characteristics.
[0064] (Example 3 and Comparative Example 4) Natural graphite CGB-10 (manufactured by Nippon Graphite Industry Co., Ltd.) as a negative electrode active material, carbon black (acetylene black Li250 manufactured by Denka Co., Ltd.) as a conductive agent, exfoliated graphite manufactured in Production Example 3 (condition 3), and BM-400B (manufactured by Zeon Corporation) and carboxymethyl cellulose (CMC) as a binder (binder) were dispersed in ion exchange water so that the solid content weight ratio of the active material, carbon black (conductive agent), exfoliated graphite (conductive agent), and binder was 89.5:0.6:3.4:6.5 to form a slurry (solid content concentration 50% by weight), and an electrode composition 6 (Example 3) was prepared. In addition, an electrode composition 7 (Comparative Example 4) was prepared in the same manner as the electrode composition 6, except that the conductive agent was changed to only carbon black (acetylene black Li250 manufactured by Denka Co., Ltd.).
[0065] Coin cells were prepared using electrode compositions 6 and 7 in accordance with the coin cell CR2032 specified in the Japanese Industrial Standard JIS C 8515. The initial discharge capacity and the discharge capacity after 80 cycles were measured at an upper limit voltage of 3.5 V and a lower limit voltage of 0.05 V. The results are shown in Figures 5 and 6, respectively.
[0066] From the results in FIG. 5, it was confirmed that when electrode composition 7 (Comparative Example 4) was used, the initial discharge capacity was 340 mAh / g, whereas when electrode composition 6 (Example 3) was used, the initial discharge capacity was 357 mAh / g, and thus the initial discharge capacity of electrode composition 6 (Example 3) was increased by approximately 5.0% compared to when electrode composition 7 (Comparative Example 4) was used.
[0067] From the results in FIG. 6, when electrode composition 7 (Comparative Example 4) was used, the discharge capacity after 80 cycles was 305 mAh / g, whereas when electrode composition 6 (Example 3) was used, the discharge capacity was 328 mAh / g. It was confirmed that the discharge capacity after 80 cycles in the case of electrode composition 6 (Example 3) was approximately 7.5% higher than that in the case of electrode composition 7 (Comparative Example 4). These results show that the use of an aqueous negative electrode composition containing the exfoliated graphite of the present invention as a conductive agent significantly increases the discharge capacity and improves the cycle characteristics. The types of electrode compositions, types of conductive agents, and discharge capacities prepared in the above Examples 1 to 3 and Comparative Examples 1 to 4 are summarized in Table 4 below.
[0068] [Table 4]
[0069] By using the exfoliated graphite of the present invention, an electrode for a lithium ion battery and a lithium ion battery including this electrode can be produced, for example, in the following manner. [Preparation of electrodes] (1) Preparation of the positive electrode The electrode composition 1 is applied to one surface of an aluminum foil serving as a positive electrode current collector by a doctor blade method, and the NMP is dried at 120° C. in an oven to prepare a positive electrode 1 .
[0070] (2) Preparation of the negative electrode Carbotron P (manufactured by Kureha Corporation) as hard carbon for the negative electrode active material, Acetylene Black Li250 (manufactured by Denka Co., Ltd.) as the conductive agent, and PVDF#9100 (manufactured by Kureha Corporation) were dispersed in an NMP solution so that the solids weight ratio of the active material, conductive agent, and binder was 91:1:8 to prepare a slurry (solids concentration: 50% by weight). The slurry was then applied to one side of copper foil as the negative electrode current collector by the doctor blade method, and the NMP was dried at 120°C in an oven to prepare a negative electrode.
[0071] [Making a lithium-ion battery] The electrolyte is prepared by dissolving LiPF6 at a ratio of 1 mole / liter in an equal volume mixed solvent of ethylene carbonate and dimethyl carbonate. A cylindrical first battery MP1 is fabricated using the positive electrode, negative electrode, and electrolyte prepared as described above (battery dimensions: diameter 14.2 mm; length 50.0 mm). Note that a microporous thin film made of polypropylene having ion permeability (manufactured by Polyplastics Co., Ltd., product name "Celgard 3401") is used as a separator.
[0072] 7 is a cross-sectional view of the first battery MP1 that was fabricated, and the first battery MP1 is composed of a positive electrode 1, a negative electrode 2, a separator 3 that separates these two electrodes, a positive electrode lead 4, a negative electrode lead 5, a positive electrode external terminal 6, and a negative electrode can 7. The positive electrode 1 and the negative electrode 2 are housed in the negative electrode can in a spirally wound state with the separator 3 filled with an electrolyte interposed therebetween, and the positive electrode 1 is connected to the positive electrode external terminal 6 via the positive electrode lead 4, and the negative electrode 2 is connected to the negative electrode can 7 via the negative electrode lead 5, so that chemical energy generated inside the first battery MP1 can be taken out as electrical energy.
[0073] From the results of Tables 3, 4, and Figs. 1 to 6, it was confirmed that the electrode composition 1 (Example 1) using the exfoliated graphite of the present invention as a conductive agent can significantly reduce the volume resistivity, and when a lithium ion secondary battery is produced using the electrode composition 1 (Example 1), the electrode composition 4 (Example 2), and the electrode composition 6 (Example 3), the discharge capacity is significantly increased and the cycle characteristics are also improved. Therefore, by producing an electrode and a lithium ion battery using an electrode composition containing the exfoliated graphite of the present invention, even if the content ratio of nickel in the active material is increased, the potential drop can be suppressed, and as a result, the corrosion of the current collector foil can be suppressed. This makes it possible to provide a lithium ion battery that can achieve high battery capacity, shortened charging time, and improved battery life. [Explanation of symbols]
[0074] 1 positive electrode 2 negative electrode 3. Separator 4 Positive Lead 5 Negative lead 6 Positive external terminal 7 Anode can
Claims
1. A conductive agent for an electrode of a lithium ion battery, the conductive agent comprising exfoliated graphite (excluding an active material) having the following characteristics (1) to (3): (1) The band intensity ratio of the Raman spectrum measured by Raman spectroscopy using an argon laser satisfies the following relationship: [G band (1580 cm -1 ) strength / D band (1360 cm -1 ) Intensity]≧8 (2) The G band of the Raman spectrum (1580 cm ) measured by Raman spectroscopy using an argon laser -1 ) half-width (G-FWHM) is 15-22 cm -1 is (3) The thickness of the basal plane of the exfoliated graphite particles is 5 to 40 nm as measured by a field emission scanning electron microscope (FE-SEM).
2. 2. The conductive agent according to claim 1, wherein the average particle size of the exfoliated graphite is 0.5 to 20 μm as measured by a laser diffraction / scattering method.
3. 3. The conductive agent according to claim 1, wherein the exfoliated graphite does not have a reactive functional group selected from the group consisting of a hydroxyl group, a carbonyl group, and a methine group on the surface thereof.
4. A conductive agent for a positive electrode of a lithium ion battery, comprising exfoliated graphite having the following characteristics (1) and (2): (1) The band intensity ratio of the Raman spectrum measured by Raman spectroscopy using an argon laser satisfies the following relationship: [G band (1580 cm −1 ) intensity / D band (1360 cm −1 ) intensity]≧8 (2) The half-width (G-FWHM) of the G band (1580 cm −1 ) of the Raman spectrum measured by Raman spectroscopy using an argon laser is 15 to 22 cm −1 .
5. The electrode composition for a lithium ion battery contains exfoliated graphite (excluding an active material) having the following characteristics (1) to (3) and a binder. (1) The band intensity ratio of the Raman spectrum measured by Raman spectroscopy using an argon laser satisfies the following relationship: [G band (1580 cm -1 ) strength / D band (1360 cm -1 ) Intensity]≧8 (2) The G band of the Raman spectrum (1580 cm ) measured by Raman spectroscopy using an argon laser -1 ) half-width (G-FWHM) is 15-22 cm -1 is (3) The thickness of the basal plane of the exfoliated graphite particles is 5 to 40 nm as measured by a field emission scanning electron microscope (FE-SEM).
6. The electrode composition according to claim 5 , further comprising carbon black.
7. The electrode composition according to claim 5 or 6, further comprising an electrode active material.
8. The electrode composition according to claim 7, which contains 0.2 to 5.5 parts by weight of exfoliated graphite per 100 parts by weight of the electrode active material.
9. A composition for an electrode of a lithium ion battery, comprising exfoliated graphite having the following characteristics (1) and (2), an electrode active material, and a binder: (1) The band intensity ratio of the Raman spectrum measured by Raman spectroscopy using an argon laser satisfies the following relationship: [G band (1580 cm −1 ) intensity / D band (1360 cm −1 ) intensity]≧8 (2) The half-width (G-FWHM) of the G band (1580 cm −1 ) of the Raman spectrum measured by Raman spectroscopy using an argon laser is 15 to 22 cm −1 . The electrode active material has the composition formula LiNi x Co y Mn z O 2 (wherein x, y and z are the molar ratios of Ni, Co and Mn, respectively, x+y+z=1, and 0.5≦x≦0.9).
10. The electrode composition according to any one of claims 5 to 9, wherein the electrode composition is a mixture composition for an electrode or a primer composition for an electrode.
11. An electrode for a lithium ion battery, comprising a current collector coated with the electrode composition according to any one of claims 5 to 10.
12. An electrode for a lithium ion battery, comprising a current collector coated with an electrode composition for a lithium ion battery, the electrode composition comprising exfoliated graphite having the following characteristics (1) and (2) and a binder, (1) The band intensity ratio of the Raman spectrum measured by Raman spectroscopy using an argon laser satisfies the following relationship: [G band (1580 cm −1 ) intensity / D band (1360 cm −1 ) intensity]≧8 (2) The half-width (G-FWHM) of the G band (1580 cm −1 ) of the Raman spectrum measured by Raman spectroscopy using an argon laser is 15 to 22 cm −1 . The electrode is a positive electrode.
13. A method for producing an electrode for a lithium ion battery, comprising depositing the electrode composition according to any one of claims 5 to 10 on a current collector.
14. A lithium ion battery comprising the electrode according to claim 11 or 12.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP1996064244A
Coating liquid used for manufacturing of electrode as well as electrode and battery manufactured by using the liquid
JP2004063423A